Full surface strain measurement using shearography - Groves, Roger M.; James, Stephen W.; Tatam, Ralph P. (International Society for Optical Engineering; 1999, 2001)
Shearography is a full-field optical technique usually used for the determination of surface strain. Correlation of interferometric speckle patterns recorded before and after the object deformation yields fringes sensitive to displacement gradient, from which the surface strain can be calculated. A full analysis of the surface strain requires the measurement of six displacement gradient components, using three illumination directions and two directions of applied shear. Additionally shearography may be used to measure surface slope by correlation of interferograms obtained before and after a source displacement to yield fringes sensitive to surface slope. Integration of the slope yields the object shape. In this paper shearography is used to measure the six components of displacement gradient of a gas main pipe under pressure, the surface slope of the pipe and the shape of the pipe. The object slope and shape are used to correct the displacement gradient measurements for variation in sensitivity vector across the object surface and for sensitivity variations due to the dependence of the applied shear upon the local slope of the object surface. A coordinate transformation, incorporating the object shape information, is used to obtain the in-plane and out-of-plane displacement gradients relative to the local profile of the surface.
Keywords: strain measurement; non-destructive testing; shearography; shape measurement